PENGARUH PERSEPSI DUKUNGAN ORGANISASI DAN PEMBERDAYAAN KERJA TERHADAP KOMITMEN ORGANISASIONAL (Studi Pada Karyawan Bagian Produksi PDAM Bandarmasih Banjarmasin) - Aida Vitria (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2017)
The aims of this research were to: 1) describe perception organizational support of employees’, 2) describe organizational commitment, 3) find out the perception organizational support and empowerment variable’s could be increasing to employees’ organizational commitment at PDAM Bandarmasih Banjarmasin city.         This research was done by using the explanatory approach which is a research approach to explain the causality or contribution of independent variable toward dependent variable through the argumentation of hypothesis way.         The descriptive result of the research showed that the PDAM Banjarmasin city still can be categorized in good condition.         While the inferential result of this research showed that perception organizational support and empowerment are influence to organizational commitment at PDAM Banjarmasin city.            For suggestion, the results of this research are expected not only to give academic contribution for the improvement of human resource, especially as a comprehension toward employees’ behavior in organization, but also to be an input for the users especially for the management section at PDAM Banjarmasin city , so they can manage the employees’ job behavior for the better organizational commitment.